The Effect of Salinity on Heavy Metal Tolerance in Two Energy Willow Varieties - Kinga Drzewiecka; Zuzanna Kaźmierczak; Magdalena Woźniak; Michał Rybak (Plants, 2025)
This study evaluated the response of two willow varieties, Salix × smithiana Willd. and Salix viminalis L. var. Gigantea, to selected heavy metals and elevated soil salinity, simulating complex environmental conditions during phytoremediation. Plants propagated from stem cuttings were cultivated in pots under field conditions in soil artificially contaminated with a mixture of Cd, Ni, Cu, Zn, and Pb salts at two concentration levels representing lower and higher guideline thresholds. Sodium chloride was added to induce salinity stress. S. × smithiana exhibited enhanced growth under combined metal and salinity stress, suggesting efficient tolerance mechanisms. This was reflected in elevated relative water content (RWC) and increased accumulation of Zn and Cd in shoots. In contrast, Gigantea showed growth inhibition and primarily sequestered metals in roots, indicating a stress-avoidance strategy and reduced metal translocation. While salinity alone negatively affected both varieties, its combination with metals mitigated growth reduction in S. × smithiana, possibly due to improved ion homeostasis or cross-tolerance. Zn and Cd displayed the highest bioconcentration and mobility. Based on bioconcentration factor (BCF) and translocation factor (TF), S. × smithiana appears suitable for phytoextraction, whereas S. viminalis var. Gigantea appears suitable for phytostabilization. These results support species-specific approaches to phytoremediation in multi-contaminant environments.